Pendampingan Penyusunan Perangkat Pembelajaran Berbasis Mobile Bagi Guru Sman 5 Bandar Lampung - Wahyudin, Achmad Yudi; Ramadhan, Rifqi (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
The industrial revolution 4.0 is a challenge for several fields of education, especially for teaching staff or teachers. With the industrial revolution 4.0 encouraging technology to develop and forcing humans to follow it, especially in the field of education, along with the development of technology and the development of the era of the world of education, new methods are needed in solve problems in it. This study aims to develop new ways of making learning devices using technology or mobile-based in accordance with the development of the era and era. This research is intended to assist teachers in facilitating the manufacture of Learning Devices and lighten the work of teachers with new methods that are rarely used in various schools. and create a method that is practical and can be accessed anywhere.